2021
DOI: 10.1021/acsami.1c04036
|View full text |Cite
|
Sign up to set email alerts
|

Optical Expediency of Back Electrode Materials for Organic Near-Infrared Photodiodes

Abstract: Organic semiconductor devices, including organic photodetectors (OPDs) and organic photovoltaics (OPVs), have undergone vast improvements, thanks to the development of non-fullerene acceptors. The absorption range of such NFA-based systems is typically shifted toward the near-infrared (near-IR) region compared to early-generation fullerene-based systems, rendering organic semiconductor devices suitable for near-IR sensing applications. While most efforts are concentrated on the photoactive materials, less atte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 53 publications
0
13
0
Order By: Relevance
“…To obtain the charge‐carrier generation rates depending on the spatial position G ( x ) in the active layer, we obtained the optical properties of the blends with variable angle spectroscopic ellipsometry (VASE) and combined them with the already known optical properties of the other materials used in the device stack to serve as the input for optical transfer matrix simulations (TMM). [ 40,52 ] The resulting G ( x ) curves are shown in Figure 3c. Here, too, a clear trend can be seen with G ( x ) being reduced noticeably as the donor concentration is reduced from 40% to 30% and 20%.…”
Section: Resultsmentioning
confidence: 99%
“…To obtain the charge‐carrier generation rates depending on the spatial position G ( x ) in the active layer, we obtained the optical properties of the blends with variable angle spectroscopic ellipsometry (VASE) and combined them with the already known optical properties of the other materials used in the device stack to serve as the input for optical transfer matrix simulations (TMM). [ 40,52 ] The resulting G ( x ) curves are shown in Figure 3c. Here, too, a clear trend can be seen with G ( x ) being reduced noticeably as the donor concentration is reduced from 40% to 30% and 20%.…”
Section: Resultsmentioning
confidence: 99%
“…Schopp et al have demonstrated, that the ideal electrode choice depends on the absorber band gap and the thickness of the active layer. Many opaque systems rely on Ag electrodes, whereas a change to Au electrodes for thin narrow-band gap active layers can boost the performance [125].…”
Section: Changes In the Interfacial Processes In Narrow Band Gap Opvsmentioning
confidence: 99%
“…In addition, both electrodes must be transparent. Although in OSC, the amount of interfacial recombination is affected significantly by the electrode choice, a broader range of materials and deposition techniques can be considered for transparent electrodes because the surface recombination at the active layer interfaces is not a dominant recombination mechanism in these systems, therefore, the limitations due to high series resistance decrease 11 . There are several ways to fabricate transparent electrodes.…”
Section: Introductionmentioning
confidence: 99%